Presumed Protective Role for Anti-Hepatitis B Virus Antibodies Against COVID-19 Severe Cases: A Clinical Study Confirming in silico Hypothesis - Gdoura, Mariem; Touati, Raoua; Kalthoum, Sana; Ben Slama, Rania; Fatnassi, Nouel; Mrad, Mehdi; Ammari, Lamia; Brahmi, Nozha; Ben Jazia, Amira; Hogga, Nahed; Triki, Henda; Haddad-Boubaker, Sondes (Frontiers in Medicine, 2022)
Abstract: Background: SARS-CoV2 is responsible for the COVID-19 disease known to have a broad clinical spectrum, from asymptomatic form to critical form leading to death. Many researchers have investigated factors impacting the course of the disease. Our previous in silico study suggested a possible protective effect of Hepatitis B, Tetanus and Measles vaccines against COVID-19. In continuity, we conducted a cross-sectional clinical study in order to confirm our in silico assumptions regarding the Hepatitis B antibodies. Methods: A representative sex and age matched sample of confirmed COVID-19 patients was selected (n=340). All clinical forms were equally represented. Using ELISA tests, each patient benefited of a serology for the detection and quantification of the anti-HBs specific IgG antibodies. Obtained results allowed determining the different correlations between these antibodies titers and the disease severity. R® software and MedCalc® software served to calculate the Spearman’s coefficient of rank correlation (rho) for the obtained titers per severity group as well as the different other calculations and figure representations. Results: A significant positive correlation was found with the anti-HBs titers (rho=0,107; p=0.04). High anti-HBs titers were significantly associated to mild form of COVID-19. A significant difference was found between the obtained titers per severity class (Chi-2 test, p = 0.03). Discussion/conclusion: Our findings demonstrated that anti-HBs titers were significantly higher for patients having mild COVID-19 forms. We presume that being immunized against the Hepatitis B may play a protective role in the course of the disease. Our study provides more key elements in understanding the disparity of the clinical spectrum among regions.